Enhancing Conceptual Understanding of Quadratic Equations through Scratch-Based Game Learning: A Constructivist Approach - Halimatu Sa'diyyah; Eyus Sudihartinih; Muhammad Faishal Faturrahman; Kakoma Luneta (Jurnal Pendidikan MIPA, 2026)
Quadratic equations are a fundamental topic in mathematics education, but various studies show that students' conceptual understanding of this material is still low. Scratch-based learning media that have been developed previously also tend to be limited to visual aspects and have not fully integrated narratives, interactive evaluations, and learning principles that support the construction of students' knowledge. This research aims to develop a Scratch-based mathematics learning media on the square equation material for class X high school students and to test its validity, practicality, and effectiveness in facilitating students' understanding of the concepts. The novelty of this research lies in the integration of interactive visuals, narratives, and game-based evaluations designed in harmony with the principles of constructivism and the cognitive needs of students. The research used the ADDIE development model, involving 19 students from class X at one of the high schools in West Bandung Regency. Data were collected through test and non-test instruments, including questionnaires from material experts, media experts, UAT, and student responses. The results of the study show that the learning media developed meet the criteria of validity, practicality, and potential effectiveness. The improvement in learning outcomes was shown by an increase in students' average scores from 38 in the pre-test to 82.1 in the post-test, with the majority of N-Gain scores in the high category. The biggest improvement occurred in contextual problem-solving skills. In addition, this media is potentially effective in helping overcome student misconceptions, especially in distinguishing between quadratic equations and quadratic functions, and is supported by positive student responses to the engagement and ease of understanding the material. Keywords: learning media, quadratic equations, scratch, ADDIE.